Intragenic recombination in a flagellin gene: characterization of the H1-j gene of Salmonella typhi. - Frankel, G (1989)
Salmonella typhi, the etiologic agent of typhoid fever, typically has only a phase-1 flagellar antigen, d, but some isolates, found only in Indonesia, have antigen j instead, and may have a second flagellar antigen, z66. It appears that intragenic recombination involving a directly repeated 11 bp sequence in the H1-d flagellin gene changed the flagellar antigen to j, by deleting 261 bp in its central, antigenically determinant, part. Sequencing of the hypervariable regions of genes H1-d and H1-j, and hybridization of such genes, after amplification by the polymerase chain reaction, with oligonucleotide probes specific for the deleted segment or for the sequence produced by the recombination confirmed that all the j alleles have the postulated deletion. By applying the polymerase chain reaction to study S. typhi isolates from Jakarta, not previously tested in respect to flagellar antigen, we showed that gene H1-j was nearly as common as H1-d in these isolates.